2017
DOI: 10.4209/aaqr.2017.05.0170
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis of Dust Transport and Budget in a Severe Asian Dust Event

Abstract: Asian dust storms markedly affect the ecosystem, environment, ocean biogeochemical cycle, and regional climate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 48 publications
(52 reference statements)
0
10
0
Order By: Relevance
“…In the present study, the impacts of natural aerosol are essentially removed. It would be useful to examine how frequently in AMJ dust aerosol layers are advected in the western North Pacific using CALIPSO Lidar dataset and the HYSPLIT model [67,68]. In addition, it is useful to consider the response to non-East Asian AA forcing on the East Asian precipitation during summer.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In the present study, the impacts of natural aerosol are essentially removed. It would be useful to examine how frequently in AMJ dust aerosol layers are advected in the western North Pacific using CALIPSO Lidar dataset and the HYSPLIT model [67,68]. In addition, it is useful to consider the response to non-East Asian AA forcing on the East Asian precipitation during summer.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The projected dust climatology carried out by Colarco et al (2014) uses the GEOS-5 general circulation model output from 2011 to 2050 and estimated the global mean dust emission annually, ranging from 1,900 to 2,400 Tg yr −1 with annual mean dust aerosol burden in a range of 20.8-23.1 Tg. MERRA-2 is shown to provide better estimates of the dust budget, including emissions, transport, and deposition (Buchard et al, 2017;Jing et al, 2017). The total mass of the dust (D L ) is calculated using the following relation.…”
Section: Reanalysis Productsmentioning
confidence: 99%
“…Dust aerosols can be transported over regional to intercontinental scales, as shown in various modeling studies (Jing et al, 2017; N. M. Mahowald et al, 2005;Todd et al, 2008;Uno et al, 2006). Previous studies also reported dust fluxes, budgets, and radiative forcing using the model simulations and reanalysis over different parts of the world (Jing et al, 2017;Todd et al, 2008;Uno et al, 2006;Zender et al, 2004). The surface layer characteristics over the Himalayan region were investigated in few recent studies (e.g., Solanki et al, 2016;Solanki et al, 2019), however, the impacts of elevated dust loadings on surface layer remain unclear.…”
mentioning
confidence: 96%
“…As a result of the assimilation of various aerosol observations, the MERRA-2 data have many advantages in the estimation and analysis of the dust load, emission and deposition in severe dust events and is an effective tool for the quantitative estimation of the dust balance in extreme dust events [39][40][41]. To understand the dust budget, we used the MERRA-2 reanalysis data to analyze the emission and the dry and wet deposition of dust in this dust event.…”
Section: Dust Budget Analysismentioning
confidence: 99%